PENYULUHAN TENTANG GIZI SEIMBANG PADA REMAJA DI PONDOK PESANTREN AL-FALAH KOTA PADANG - Saputra, Muhammad Rizki; Rifkind Malik; Betty Fitriyasti; Sri Wahyuni; Suharni (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Adolescence is a period of human growth and maturity. During adolescence, apart from physical changes, mental and emotional changes also occur which change very quickly. Growth during adolescence demands balanced nutritional needs to achieve maximum growth. Adolescent health and nutrition an important aspects in adolescent life which is the basis of the human life cycle. Lack of understanding among teenagers regarding information on nutrition, health, and other social life problems, so it is necessary to provide education regarding balanced nutrition. The methods used in this service activity are presentations and lectures, discussions, and questions and answers. During this socialization, the students were very enthusiastic about listening to counseling about balanced nutrition for these teenagers. This is proven by the many questions that arise regarding the material presented. This service activity can be considered a very useful activity in efforts to increase teenagers' knowledge about balanced nutrition. Keywords: Balanced nutrition, teenagers, Islamic boarding school